Remarkable discoveries! - Ashall, Frank 1957- (Cambridge University Press, 1994)
Remarkable Discoveries shows how scientists have made great discoveries that have pushed back the frontiers of knowledge and have changed the way we look at the world. Frank Ashall, scientist and writer, takes us on a magical mystery tour of eighteen major scientific discoveries. Electricity, X-rays, DNA fingerprinting and the Big Bang are but a few of the achievements on which the author writes. We delve into the world of the researcher and experience the excitement as each discovery is unfolded. Can we thank chance or just intelligence and hard work for the scientists' success? The personalities, the trials, the triumphs are all here. Remarkable Discoveries takes the reader on an exhilarating tour through some of the major scientific discoveries that have benefited humanity